If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (b + 4)(b + -15) = 0 Reorder the terms: (4 + b)(b + -15) = 0 Reorder the terms: (4 + b)(-15 + b) = 0 Multiply (4 + b) * (-15 + b) (4(-15 + b) + b(-15 + b)) = 0 ((-15 * 4 + b * 4) + b(-15 + b)) = 0 ((-60 + 4b) + b(-15 + b)) = 0 (-60 + 4b + (-15 * b + b * b)) = 0 (-60 + 4b + (-15b + b2)) = 0 Combine like terms: 4b + -15b = -11b (-60 + -11b + b2) = 0 Solving -60 + -11b + b2 = 0 Solving for variable 'b'. Factor a trinomial. (-4 + -1b)(15 + -1b) = 0Subproblem 1
Set the factor '(-4 + -1b)' equal to zero and attempt to solve: Simplifying -4 + -1b = 0 Solving -4 + -1b = 0 Move all terms containing b to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1b = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1b = 0 + 4 -1b = 0 + 4 Combine like terms: 0 + 4 = 4 -1b = 4 Divide each side by '-1'. b = -4 Simplifying b = -4Subproblem 2
Set the factor '(15 + -1b)' equal to zero and attempt to solve: Simplifying 15 + -1b = 0 Solving 15 + -1b = 0 Move all terms containing b to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -1b = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -1b = 0 + -15 -1b = 0 + -15 Combine like terms: 0 + -15 = -15 -1b = -15 Divide each side by '-1'. b = 15 Simplifying b = 15Solution
b = {-4, 15}
| 4x+7=6(x-7)+3x | | 14=6x-3x+2 | | 9h-15=30 | | tan65=x/20 | | 2(2a+1)=3a | | X+(2y+24)=180 | | m^2-12m+9= | | cos55=10/x | | 0=2x+3.4 | | 84=2l*2w | | (4-lnx)*lnx=0 | | 4x^2-sqrt(5x)-2=0 | | -9+5x=16 | | 2x.1/2=90.1/2 | | 1/(8x) | | (7/9)/(5/8) | | Y=10/7*3-10 | | 12a+6(4-7a)=9(2a+4) | | 6r+35+11r= | | (5-6i)(5+6i)= | | 16a+b-7a+11b= | | 5x=y-31 | | 4a+3b+2C=15.5 | | -10x+4=24 | | x+2(128)=197 | | 6.29999995/2.1 | | 0=-16x^2+144x+160 | | -12m+7=31 | | 3=x/2.1 | | L*W=84cm | | l*w=84 | | -4+5-1=-2a+3a |